A further enhancement of K-Medoid clustering algorithm applied on blood donor behavior segmentation - Francis Earl S. Fojas andAna Mikaela A. Vilar. 4 0 16; 5
u
Thesis: (BSCS major in Computer Science)- Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2